THE RELATIONSHIP BETWEEN BADMINTON SKILLS AND STUDENTS' SOCIAL-EMOTIONAL DEVELOPMENT - Randi Saputra Ibrahim; Hasrat A Aimang; Martono (JURNAL PENDIDIKAN GLASSER, 2025)
Physical education plays a crucial role in shaping the character and physical skills of elementary school students. One of the sports that can support the development of both motor skills and socio-emotional aspects is badminton. This study aims to investigate the relationship between badminton skills and the socio-emotional development of students at SDN 9 Luwuk in Banggai Regency. The research uses a quantitative approach with a survey method, collecting data through questionnaires and skill tests. Data analysis was conducted using descriptive and inferential statistics, including Pearson’s correlation analysis to assess the relationship between the two variables. The results show that 80% of students have adequate basic badminton skills, although there are weaknesses in serve techniques and ball return. Regarding socio-emotional development, 70% of students demonstrated good teamwork skills, but only 55% were able to manage their emotions well during matches. The correlation analysis revealed a moderate positive relationship between badminton skills and socio-emotional development (r = 0.68; p < 0.05), indicating that badminton skills contribute to the improvement of social skills and emotional regulation. This study provides significant contributions to understanding the role of sports, particularly badminton, in supporting socio-emotional development in elementary school students. The conclusion of this study highlights the importance of integrating sports into the physical education curriculum to enhance both physical and socio-emotional development simultaneously. Future research should explore the impact of individual sports on the socio-emotional development of children in more depth.